Strategy Formulation Through Value Chain - Lionora, Clarisa Alfa; Aprilistyan, Syifaa Freza; Saputri, Sonia Aprilia (Universitas Tidar, 2023)
The rapid development of the business world has made competition between business units increasingly fierce. To overcome this, each business unit is required to survive in the competition by having a competitive advantage. The purpose of this study is to analyze how the form of competitive advantage of the Lurik Asik business unit. The research method used is a qualitative method. The research approach is carried out through case studies. The data used in this study is primary data. The data acquisition method used is an in-depth interview. The final result of this research is the formulation of a business strategy in order to increase the competitive advantage of a business unit. The results of the study have implications for business units to use strategies through innovation, stock management, production process efficiency, the importance of lurik cloth in the eyes of customers, and the prestige of lurik cloth in the fashion world to have a competitive advantage so that it will be able to survive in market competition and become a business unit that is competitive sustainable. Keyword: Competitive Advantage; Lurik; Value Chain Analysis, VRIO Analysis JEL Classification: